Overview of G3: Water Governance and Community Based Management - CGIAR Challenge Program on Water and Food (2012)
The International Water Management Institute is the lead institute for the Ganges Basin Development Challenge research project titled Water Governance and community-based management in coastal regions of Bangladesh. This study is one out of five research projects in the Ganges basin commissioned and funded by the CGIAR challenge Program on Food and Water inundation, salinity intrusion and severe flooding in the coastal areas is a frequent occurrence in Bangladesh. This leads to loss of life and property as well as severe impacts on livelihoods. the government of Bangladesh has invested steadily in coastal zone management through construction and rehabilitation of polders. involvement of communities in management of polders is now enshrined in Bangladesh’s Water Policy. this project tries to understand various aspects of water governance and communities based management of polders in coastal zones in Bangladesh and then suggest implementable policy options for improving polder governance in Bangladesh.